2008
DOI: 10.2174/157340108783497427
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors Influencing Magnesium Absorption in Humans

Abstract: Decreased Mg intake and low Mg status have been associated with a number of major health concerns such as diabetes mellitus type II, coronary heart disease, and osteoporosis. While information on Mg intake is available, relatively little is known on dietary factors influencing Mg bioavailability. While it is established that Mg absorption is based on a combination of a non-saturable and a saturable pathway, the nature of especially the latter mechanism is not well understood. Recently, stable isotopes have imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 210 publications
(219 reference statements)
0
24
0
Order By: Relevance
“…Similarly, in another study among Australian general Practice Registrars, the majority (90%) indicated that reducing saturated fats was a "highly appropriate" strategy in preventing and managing hypertension conditions [29]. It is important to note that another effect of high intake of fatty foods containing high proportions of long-chain fatty acids is its capability of lowering the absorption of magnesium [33].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another study among Australian general Practice Registrars, the majority (90%) indicated that reducing saturated fats was a "highly appropriate" strategy in preventing and managing hypertension conditions [29]. It is important to note that another effect of high intake of fatty foods containing high proportions of long-chain fatty acids is its capability of lowering the absorption of magnesium [33].…”
Section: Discussionmentioning
confidence: 99%
“…Oils and fats are hydrolyzed enzymatically in the body by lipases found in the mouth (lingual lipase), stomach (gastric lipase), and intestine (pancreatic lipase). These lipases hydrolyze triglycerides at sn-1 and sn-3 position [9,25,26].…”
Section: Optimum Incubation Time Of Vco Enzymatic Hydrolysismentioning
confidence: 99%
“…On the other hand, MCT is quickly hydrolyzed, begins in the mouth by lingual lipase, and continues in the stomach by gastric lipase then absorbed into the liver through portal vein, and hence, most hydrolyzed product do not reach the small intestine. Calcium and magnesium can react with LCFA generated from LCT oils hydrolysis to form insoluble mineral salts, which are not absorbed by intestine mucous, hence excreted through the feces [9,10,29,30].…”
Section: Margata Et Almentioning
confidence: 99%
“…Fatty acids, mainly from the hydrolyzed long-chain triglycerides (LCTs), can react with calcium and magnesium in the intestine to form insoluble salts. These salts are unable to be absorbed, and hence, excreted through the feces [8][9][10].…”
Section: Introductionmentioning
confidence: 99%